In essential hypertension, a change in the renal resistive index is associated with a change in the ratio of 24-hour diastolic to systolic blood pressure - Svěcený, Jakub; Charvát, Jiří; Hrach, Karel; Horáčková, Miroslava; Schück, Otto (Physiological research, 2022)
An increase in the renal resistive index (RRI) in patients with essential hypertension (EH) predicts deterioration in renal function. In patients with EH, changes in hemodynamic parameters significantly affect the RRI. This study aimed to define changes in Ambulatory Blood Pressure Monitoring (ABPM) parameters that are significantly associated with a change in RRI in patients with EH. We evaluated ABPM and the RRI in 96 patients with EH without organ extrarenal changes at baseline and after two years of follow-up. The relationships between changes in ABPM parameters and the RRI over the period were evaluated. After two years of follow-up, the increase in RRI was consequential. Simultaneously, 24-h systolic blood pressure increased significantly and 24-h diastolic blood pressure decreased. In the whole group and in the group with calculated cystatin C clearance (eGFRcyst) >/=90 ml/min/1.73 m2, the change in RRI significantly negatively correlated with the change in the ratio of 24-h diastolic to systolic blood pressure (D/S ratio), but also with the change in 24-h pulse blood pressure. However, in patients with eGFRcyst>90 ml/min/1.73 m2, only the change in the 24-h D/S ratio significantly correlated with the change in RRI. Based on the backward stepwise regression analysis, the change in RRI was significantly dependent only on the change in 24-h D/S ratio and not on the change in 24-h pulse pressure. A change in the ratio of diastolic to systolic pressure better reflects a change in RRI than a change in pulse pressure.
Keywords: krevní tlak; ambulantní monitorování krevního tlaku; Kidney; cévní rezistence; esenciální hypertenze; lidé; hypertenze; Hypertension; Vascular Resistance; Blood Pressure; ledviny; Blood Pressure Monitoring, Ambulatory; Essential Hypertension; Humans